The PD-1/PD-L1 Inhibitory Pathway is Altered in Primary Glomerulonephritides - Grywalska, Ewelina; Smarz-Widelska, Iwona; Krasowska-Zajac, Ewelina; Korona-Glowniak, Izabela; Zaluska-Patel, Karolina; Mielnik, Michal; Podgajna, Martyna; Malm, Anna; Rolinski, Jacek; Zaluska, Wojciech (Archivum Immunologiae et Therapiae Experimentalis, 2018)
The pathogenesis of primary proliferative and non-proliferative glomerulonephritides (PGN and NPGN) is still not fully understood, however, current evidence suggests that most cases of PGN and NPGN are the results of immunologic response to different etiologic agents that activates various biological processes leading to glomerular inflammation and injury. Programmed cell death protein 1 (PD-1) is the major inhibitory receptor regulating T cell exhaustion. The aim of this study was to evaluate the frequencies of PD-1-positive and PD-ligand 1 (PD-L1)-positive T and B lymphocytes in patients with NPGN and PGN in relation to clinical parameters for the first time. The study included peripheral blood (PB) samples from 20 newly diagnosed PGN and NPGN patients. The control group comprised of 20 healthy age- and sex-matched subjects. The viable PB lymphocytes underwent labelling with fluorochrome-conjugated monoclonal antibodies anti-PD-1 and anti-PD-L1, and were analyzed using a flow cytometer. The frequencies of CD4 + /PD1 + T lymphocytes, CD8 + /PD1 + T lymphocytes, and CD19 + /PD-1 + B lymphocytes in the PGN group exceeded values obtained both in the NPGN group, and the control group. Alteration of PD-1/PD-L1 pathway may be involved in poorer prognosis, as patients with PGN are characterized by higher frequencies of PD-1-positive and PD-L1-positive T and B lymphocytes than patients with NPGN. Our results suggest that deregulation of PD-1/PD-L1 axis may contribute to the PGN and NPGN pathogenesis. High percentages of lymphocytes with PD-1 and PD-L1 expression may be related to the continuous T-cell activation and development of glomerular inflammation and injury.